Dietary shift for juvenile freshwater redclaw crayfish (Cherax quadricarinatus): A review - Kurniawan, Andri; Adibrata, Sudirman; Lingga, Rahmad; Setiadi, Jhodi; Hidayah, Reysya S N; Wulandari, Ufi A (Aquaculture, Aquarium, Conservation & Legislation, 2024)
The freshwater crayfish (Cherax quadricarinatus von Martens, 1868), also known as the redclaw, is a freshwater lobster (crustacean) that has the potential to be developed as a consumption commodity. The development of lobster cultivation can be carried out using an intensive system. The juvenile production is one of the important keys to produce lobster in consumption size. The productivity of the juvenile stage must be supported by growth and survival. Appropriate feed is one of the important keys that influences the growth and survival of juvenile. Information regarding the nutrients needed by juvenile has to be conveyed in a comprehensive manner to be useful for lobster cultivation development efforts. This review article aims to elaborate on nutrient requirements and the metabolic role of these nutrients for juvenile redclaw. The review was carried out by studying various Indonesian national and international articles, which discussed redclaw related subjects, such as natural food and the role of feed nutrients in the growth of juvenile. The review results show that one of the important problems in the aquaculture of redclaw was the growth and survival of juveniles. Juveniles showed non-selective feeding behavior. However, there was ontogenetic dietary shift. Redclaw feeding habits were characterized by exogenous feeding and, in general, detritivorous or omnivorous. Naturally, redclaw fed mostly on decayed plants and animals, macroinvertebrates, detritus, macrophytes, and fish. Juvenile redclaw showed filter-feeding and scraping behavior, being non-selective feeders. In cultivation environments, some studies have shown that juvenile redclaw fed on Alona sp., Daphnia sp., Artemia sp., blood worms, silkworm, and some combinations with other organic matter such as rice flour, carrot, golden snail, earthworms, and anchovies. There was a relationship between the composition of nutrients and feeding habit, ontogenetic dietary shift, and its metabolism of enzymes. Juvenile redclaws need proteins more than carbohydrates and lipids, although the overall nutrient intake of vitamins and minerals is important for growth and survival.